A prospective study of transdiagnostic psychiatric symptoms associated with burnout and functional difficulties in COVID-19 frontline healthcare workers. (August 2022) - Kachadourian, Lorig; Murrough, James; Kaplan, Carly; Kaplan, Sabrina; Feingold, Jordyn; Feder, Adriana; Charney, Dennis; Southwick, Steven; Peccoralo, Lauren; DePierro, Jonathan; Ripp, Jonathan; Pietrzak, Robert
Abstract: Objective: Frontline healthcare workers (FHCWs) responding to the COVID-19 pandemic develop posttraumatic stress disorder (PTSD), major depressive disorder (MDD) and generalized anxiety disorder (GAD) symptoms. Such symptoms are associated with burnout, occupational and relational difficulties. In the current study, we examined the prospective association between acute transdiagnostic COVID-19-related PTSD, MDD, and GAD symptoms at pandemic outset, and burnout and functional difficulties several months later in FHCWs in New York City. Methods: Wave 1 symptoms of COVID-19-related PTSD, MDD, and GAD, were assessed in 787 FHCWs from April 14 to May 11th, 2020. Burnout and occupational difficulties were assessed at wave 1 and wave 2, approximately 7 months later. Results: After adjusting for wave 1 burnout, wave 1 MDD symptoms, particularly sleep difficulties, loss of interest, and feeling tired/having little energy, collectively explained 42% incremental variance in this outcome. After adjusting for wave 1 work difficulties, MDD and PTSD symptoms, particularly feeling tired/having little energy, loss of interest, and negative expectations of self/world, collectively explained 42% incremental variance in this outcome. After adjusting for wave 1 relationship difficulties, MDD, GAD, and PTSD symptoms, particularly depressed mood, irritability, and appetite disturbance, explained 26% incremental variance in this outcome. Conclusions: Results highlight psychiatric symptoms assessed during the acute phase of the COVID-19 pandemic that may help predict burnout and work and relationship difficulties in FHCWs. Early interventions aimed at ameliorating transdiagnostic symptoms of MDD, PTSD, and GAD may help mitigate risk for burnout and functional difficulties in this population.